Pengembangan Medialog Sebagai Media Kampanye Moderasi Beragama Bagi Kaum Milenial - Ajuan Tuhuteru; Lilis Sukmawati; Eni Murdiati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
The presence of new media changes all of human life, including in terms of accessing information. The concept of religious moderation has become the government's priority in building public awareness about diversity, but it is still not optimal in targeting all groups. Therefore there is a need for elaboration in a study. This article aims to determine the development of digital blog-based media as a media campaign for religious moderation, which is abbreviated as â€œMeDiaLogâ€, the feasibility and practicality of this media campaign. The research method used is a type of research and development (Research and Development) with the ADDIE development model. MeDiaLog feasibility test or validation is carried out by content experts, media experts, and users. The MediaLog trial was carried out in two stages: a small group trial involving 15 people, while a large group trial involving 100 people. The research results obtained from the development of blog-based digital media as campaign media, after going through the stages of analysis, planning/design, and development that have been approved by material experts and media experts can be seen on the blog link: https://maluku-rumahmoderasi-beragama.blogspot.com/. Furthermore, for feasibility, after being assessed by material experts and media experts, a value of 4.85 was obtained in the very good category by material/content experts, while media experts with an average score of 3.8 were in the good category. While the small group limited trial found an average value of 4.205 in the Good category. Next, for the practicality of the medialog itself, after conducting a large group limited trial, the average score for the material aspect and display aspect was 4.325, which is in the very good category. Thus, it can be concluded that MeDiaLog as a medium for campaigning for religious moderation has been tested for its feasibility as a media campaign